Reforms of Music Culture Education - Ibragimovich , Mustafoev Bakhtiyor (International Journal of Psychosocial Rehabilitation, 2020)
In the article, the content and essence of the reforms carried out in the field of music culture education in Uzbekistan, improvement of music education in secondary schools, professional competence of the teacher of music culture, pedagogical conditions of organization of modern lessons, techniques, methods and tools were discussed.